2019
DOI: 10.1016/j.physletb.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Charm-baryon production in proton-proton collisions

Abstract: Recent measurements of charm-baryon production in proton-proton collisions at the LHC have found a surprisingly large yield relative to those of D-mesons. We propose that this observation can be explained by the statistical hadronization model (SHM), by employing a largely augmented set of charm-baryon states beyond the current listings of the particle data group. We estimate the additional states using guidance from the relativistic quark model and from lattice QCD. Using charm-and strange-quark fugacity fact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 41 publications
9
98
0
Order By: Relevance
“…This then leads to a yield of 0.547 for Λ + c and 0.175 for Ξ c as shown in Table V. The total integrated yield ratio Λ + c /D 0 is then about 0.64, which is slightly larger than the value of about 0.54 measured in p + p collisions at √ s = 7 TeV at LHC [21,48]. We note that the oscillator constant used here for charmed baryons is larger than that for charmed mesons, which is different from that in Ref.…”
Section: Resultsmentioning
confidence: 79%
“…This then leads to a yield of 0.547 for Λ + c and 0.175 for Ξ c as shown in Table V. The total integrated yield ratio Λ + c /D 0 is then about 0.64, which is slightly larger than the value of about 0.54 measured in p + p collisions at √ s = 7 TeV at LHC [21,48]. We note that the oscillator constant used here for charmed baryons is larger than that for charmed mesons, which is different from that in Ref.…”
Section: Resultsmentioning
confidence: 79%
“…For non-strange D-mesons (D and D * ), the hadrochemistry does not show significant variations from pp to p-Pb and Pb-Pb collisions, and essentially follows that of a statistical hadronization with relative weights given by thermal factors at a "hadronization temperature" of T H 160 MeV. The D s /D ratio is also compatible with this pattern, once a strangeness suppression factor of γ s 0.6, as independently inferred from strange-particle production, is accounted for in pp collisions [150]. In semi-/central A-A collisions γ s is close to 1 (which is believed to be a consequence of strangeness equilibration in the QGP fireball), and the expected increase of the D s /D ratio in A-A collisions [151][152][153] is indeed compatible with experimental observations [154].…”
Section: Hf Hadrochemistrymentioning
confidence: 56%
“…In Ref. [150] it was shown that upon including a largely augmented charm-baryon spectrum as predicted by relativistic quark models (also consistent with lQCD [157]), the ALICE measurement could be accounted for. Improvements in the string fragmentation scenario, by accounting for color correlations beyond the leading-color approximation to create several MPI subsystems, can also facilitate the formation of charm baryons in pp collisions [113], yielding a Λ c /D 0 ratio close to that measured at midrapidity.…”
Section: Hf Hadrochemistrymentioning
confidence: 97%
“…On the other hand, the r BM value for heavy flavor hadrons is set to 1.00, because the light flavor value of 0.53 would lead to too few charm baryons (by a factor of ∼ 4) compared to the experimental data in pp or AA collisions. In principle, the r BM value for charm hadrons is related to the properties such as the number and masses of available charm baryon states versus charm meson states, and the higher r BM value for charm is consistent with the assumption that relative to light flavors there are more charm baryon states than charm meson states [40].…”
Section: Descriptions Of Heavy Flavors In the Updated Ampt Modelmentioning
confidence: 93%